The G20 is not just a G7 with extra chairs - Agnès Bénassy-Quéré; Rajiv Kumar; Jean Pisani-Ferry (Bruegel, 2009)
The G20 is not just a G7 with Extra Chairs is a joint paper written by Agnes Benassy-Quere, Rajiv Kumar and Jean Pisani-Ferry (Director of Bruegel) following the International Cooperation in Times of Global Crisis: Views from G20 Countries conference in Delhi on 14th and 15th of September, organised by Bruegel, CEPII and ICRIER. The publication draws together the authors` conclusions from the Delhi conference and reviews the real role of the G20, while questioning where the non-G7 interests fit into the group`s agenda.
Keywords: 330; Finanzmarktkrise; Internationale wirtschaftspolitische Koordination; Internationaler Finanzmarkt; Regulierung; Zahlungsbilanzungleichgewicht; G-20-Staaten